MOTIVATIONS FOR CHOOSING TO STUDY TOURISM AND HOSPITALITY MANAGEMENT: A COMPARISON OF MAINLAND CHINESE AND TAIWANESE UNDERGRADUATE STUDENTS - ZHI GUO, YING-; CHING WANG, KUO-; LI, LEI; SONG, SHULING (ITB Journal Publisher, LPPM ITB, 2005)
More and more students choose Hospitality and Tourism Management (HTM) as their subject field in the universities and colleges in both Mainland China and Taiwan. The objective of this study was to investigate motivations of undergraduate students in choosing a HTM program for both Mainland China and Taiwan. The result of a factor analysis identified five factor domains for undergraduate students in both places. A cluster analysis produced four distinc-tive clusters for undergraduate students. Differences between Mainland Chinese and Taiwan-ese students were revealed in their motivations in choosing a HTM program, behaviors and attitudes toward HTM, and a socio-demographic variable. The study results hold useful impli-cations for educational researchers and for strategies for educational administrations in both Mainland China and Taiwan.